Detection of Salmonella spp. in retail meat products: a comparison between a discontinued commercial kit and a laboratory‐developed screening method. (1st August 2019) - Shushe, O.; Wroblewski, D.; MacGowan, C.E.; Passaretti, T.; Musser, K.; Mingle, L.
Abstract: The National Antimicrobial Resistance Monitoring System for Enteric Bacteria retail food surveillance programme screens retail meat samples for the presence of Salmonella spp. to track antimicrobial resistance in food. In this study, a laboratory developed real‐time PCR assay that detects Salmonella spp. was evaluated as a screening method to replace the discountinued 3M TECRA kit. The 3M TECRA kit was a commercially available, visual immunoassay used to screen food samples for the presence of Salmonella spp . This kit was discontinued in September 2016 by the manufacturer and an alternative screening method was needed to replace the discontinued TECRA kit. Salmonella spp. is detected by the real‐time PCR assay earlier in the screening process than by the TECRA kit. Salmonella spp . can also be reliably isolated from the enrichment broth earlier in the protocol. Additionally, cost analysis shows that the real‐time PCR assay saves 2·50 per sample. New York State Department of Health currently uses this real‐time PCR assay as a screening method for the presence of Salmonella spp . in retail meat samples. The assay allows for continued monitoring of antimicrobial resistance in Salmonella spp., while providing a cost savings and a decrease in turnaround time. Significance and Impact of the Study: The National Antimicrobial Resistance Monitoring System for Enteric Bacteria (NARMS) tracks antimicrobial susceptibility of enteric bacteria in people, food and animals (https://www.fda.gov/animalveterinary/safetyhealth/antimicrobialresistance/nationalantimicrobialresistancemonitoringsystem/ ). The New York State Department of Health (NYSDOH) became a NARMS retail food surveillance (RFS) site in 2003. The NARMS‐RFS programme screens retail meat samples from grocery stores in the United States for the presence of Salmonella spp. and other enteric pathogens to monitor the prevalence of antimicrobial resistance among these pathogens. The NYSDOH developed a rapid and cost‐effective real‐PCR assay to screen for Salmonella spp. in retail meat products.